PENGARUH KEPUASAN KERJA TERHADAP KINERJA INDIVIDUAL DENGAN SELF ESTEEM DAN SELF EFFICACY SEBAGAI VARIABEL INTERVENING - CECILIA ENGKO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2008)
This study examines the effect of job satisfaction on job performance with self esteem and self efficacy as an intervening variable. The purpose of this study is to find empirical evidence about the presence of a) the positive effect of job satisfaction on self esteem, b) the positive effect of job satisfaction on self efficacy, c) the positive effect of job satisfaction on job performance, d) the positive effect of self esteem on self efficacy, e) the positive effect of self esteem on job performance, f) the positive effect of self efficacy on job performance. The respondents of this study are the students of Magister Science of Gajah Mada University, especially those who are lecturer that come from many universities in Indonesia. The collecting data used the direct distribution questionnaire. Data were analyzed using path analysis. The result from this study are the positive effect of job satisfaction on self esteem, job satisfaction on self efficacy, job satisfaction on job performance, self esteem on self efficacy, self efficacy on job performance.